2007
DOI: 10.1016/j.neulet.2007.01.065
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol withdrawal posttranslationally decreases the activity of cytochrome c oxidase in an estrogen reversible manner

Abstract: Cytochrome c oxidase (COX) is a key mitochondrial enzyme that catalyzes electron transfer at the terminal stage of respiratory chain and is composed of multisubunits. We hypothesize that ethanol withdrawal (EW) impairs the activity of COX and estrogen deprivation exacerbates this problem. Five month-old ovariectomized rats with or without 17β-estradiol (E2) replacement received a control dextrin or a liquid ethanol diet (6.5%, five weeks). They were then sacrificed either during ethanol exposure or at 24 hours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…We observed previously that EW inactivated a key mitochondrial enzyme, cytochrome c oxidase, and provoked oxidation of mitochondrial proteins in rats (Jung et al, 2007(Jung et al, , 2008). In the current study, we used an in vitro HT22 cell model because this cell line has the advantage of assessing oxidative mechanisms.…”
Section: Discussionmentioning
confidence: 84%
“…We observed previously that EW inactivated a key mitochondrial enzyme, cytochrome c oxidase, and provoked oxidation of mitochondrial proteins in rats (Jung et al, 2007(Jung et al, , 2008). In the current study, we used an in vitro HT22 cell model because this cell line has the advantage of assessing oxidative mechanisms.…”
Section: Discussionmentioning
confidence: 84%
“…Furthermore, we have demonstrated that EW inactivates the key respiratory complex cytochrome c oxidase (17) and accelerates swelling and rupture of brain mitochondria from ovariectomized female rats experiencing EW (20). Moreover, the identical IH regimen attenuated EW signs and oxidative stress in female rats (18).…”
Section: Discussionmentioning
confidence: 98%
“…This suggests that the aged cerebellum may be even more vulnerable to ethanol-induced mitochondrial dysfunction than the young adult cerebellum. A recent report (212) suggested that ethanol withdrawal, rather than ethanol exposure per se, decreases the activity of cytochrome c oxidase in adult rat cerebellum. The ethanol/withdrawalinduced defects in mitochondrial energy metabolism may disturb several vital neuronal functions, e.g., by generation of ROS, or by impairment of membrane integrity, which increases vulnerability to excitotoxic neuronal injury (161,207,213).…”
Section: Mitochondrial Damage and Impaired Energy Metabolismmentioning
confidence: 99%